A sustainable public healthcare model: Transformative Resilience and crisis management in a State University Hospital during the coronavirus pandemic - Andri Syahreza; Rachmadi Purwana; Tri Edhi Budhi Soesilo (ASEAN Natural Disaster Mitigation and Education Journal, 2026)
Background: The problem is rooted in the governance paradox of State University Hospitals, which are hierarchical and rigid when facing the exponential escalation of the coronavirus pandemic. This condition triggered an absolute scarcity of critical resources, threatening cascading failures in hospital operations. The objective of this research is to evaluate surge capacity adaptation strategies, measure preparedness parameters, and analyze the effectiveness of multisectoral coordination in creating organizational resilience. Methods: This study used a descriptive qualitative method with a case study approach through in-depth interviews, observation, and document review. The analysis was conducted by evaluating the preparedness parameters using a scoring system, followed by the After-Action Review (AAR) and Pattern Matching methods. Findings: The findings indicate that the hospital reconstructed its resource allocation system. A critical weakness was detected in the initial logistics supply, while an emergency budget plan expanded rescource allocation capacity. Multisectoral coordination through a three-pillar synergy reduced functional isolation and supported an adaptive organizational structure. Conclusion: The hospital has surpassed the survival phase towards the transformative resilience phase. Crisis experiences have been institutionalized into permanent policies within the strategic plan, making the institution more resilient in facing future disaster threats. Novelty/Originality of this article: This study provides a novel approach by integrating the conceptual framework of surge capacity, including space, staff, supplies, and systems with disaster preparedness measurement standards to produce a comprehensive hospital resilience blueprint for developing countries.